Engineered nanoselenium supplemented fish diet: toxicity comparison with ionic selenium and stability against particle dissolution, aggregation and release. Issue 8 (25th June 2020) - Abdolahpur Monikh, Fazel; Chupani, Latifeh; Smerkova, Kristyna; Bosker, Thijs; Cizar, Petr; Krzyzanek, Vladislav; Richtera, Lukas; Franek, Roman; Zuskova, Eliska; Skoupy, Radim; Darbha, Gopala Krishna; Vijver, Martina; et al.
Abstract : Transformation of nutrients to their nano-form, such as selenium (Se) engineered nanonutrients (Se-ENNs), is expected to enhance the absorption of the nutrients into fish and increase the efficiency of the feed. Abstract : Transformation of nutrients to their nano-form, such as selenium (Se) engineered nanonutrients (Se-ENNs), is expected to enhance the absorption of the nutrients into fish and increase the efficiency of the feed. However, dissolution, aggregation, and release of ENNs from the feed matrix may decrease the efficiency of the Se-ENNs. In this study, we provided fish feed supplemented with Se-ENNs which do not aggregate or dissolve and the particles are also not released from the feed matrix. As a proof of principle, we compared the toxicity of a diet containing Se-ENNs of two different sizes (60 nm and 120 nm) with diets containing ionic Se. The adverse effects were measured by monitoring the survival rate, acetylcholinesterase (AChE) levels and swimming behavior of zebrafish over 21 days of feeding with either the Se-ENNs or ionic Se supplemented fish diets. The number size distribution of the 60 nm Se-ENNs in the diet was similar to that in MilliQ water, while the size distribution of the 120 nm Se-ENNs in the diet was slightly wider. Ion and particle release from Se-ENNs containing diets in the exposure media was not observed, indicating the stability of the particles in the feed matrices. To determine toxicity, zebrafish ( Danio rerio ) were nourished using a control diet (without Se and Se-ENNs), Se (sodium selenite) containing diets (with 2.4 or 240 mg Se per kg feed) and Se-ENNs containing diets (with 2.4 or 240 mg Se-ENNs of 60 or 120 nm per kg feed) for 21 days. Both sizes of Se-ENNs were taken up in the fish, however only the 120 nm Se-ENNs were detected in the brains of fish. Zebrafish fed with Se-ENNs supplemented diets (60 and 120 nm) showed normal swimming behavior compared to the control. No significant alteration was determined in the AChE activity of the fish fed with the Se-ENNs supplemented diet. In contrast, feeding the zebrafish with a diet containing 240 mg kg −1 Se led to lethal effects. These observations clearly depict the potential benefits of using Se-ENNs as nutrients in fish feed.